Social dominance and milking behaviour in dairy goats - Ney, Jessica Ann; Müller, Corinna; Kaufmann, Otto (Animal welfare, Ethology and Housing Systems (AWETH), 2009)
Social dominance and milking behaviour in three dairy goat herds belonging to the White German Improved breed were investigated. The aims of this study were to analyse the complex relationships between social rank, milking order and milk yield. Furthermore, the behaviour in the milking parlour regarding different social ranks and stimulation during milking (hand stimulation, no stimulation, mechanical stimulation) was observed. Additionally, the occurrence and function of intervention behaviour were examined. The observations took place before, during and after the morning milking. Non-linear hierarchies consisting of circular relationships could be defined in all three herds. Intervenors were either high ranking or higher ranking than at least one of the competitors. Social rank affected the milking order in that higher ranking individuals tended to front positions in the milking parlour. Milk yield and behaviour in the milking parlour were not dependent on social rank. The animals reacted stronger towards mechanical stimulation during milking suggesting that this procedure was unpleasant.